Pengaruh Motivasi dan Kepuasan Kerja Terhadap Kinerja Pegawai Pada Dinas Pendidikan Kabupaten Tanjung Jabung Barat - Kasiyati Yunita Wulansari (Universitas Batanghari Jambi, 2019)
The title raised in this study is the Effect of Job Motivation and Satisfaction on Employee Performance at the Education Office of West Tanjung Jabung Regency. This study aims to determine the effect of Motivation and Job Satisfaction on Employee Performance at the Tanjung Jabung Barat District Education Office. Testing is done using multiple linear regression analysis. Hypothesis testing is done by using t test and F test. The magnitude of the effect is known through testing the coefficient of determination. Based on the discussion it can be concluded that the effect of Motivation (X1) and Job Satisfaction (X2) together on Performance (Y) is 13.275%. In the t test, the effect of Motivation (X1) and Job Satisfaction (X2) has a partial effect on Performance (Y). in the F test, Motivation (X1) and Job Satisfaction (X2) have a simultaneous influence on performance (Y).